(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
The article analyses the syntactic relationship in traditional and structural linguistics. The syntactic relationship serves to express syntactic attitudes and show the great importance in sentence analysis. The relationship is statistic in traditional linguistics; however, it becomes dynamic in structural linguistics. The syntactical relationship is in a linear order in traditional linguistics, but the relationship in structural linguistics is developed in a hierarchical order.